A social-legal analysis of the realisation of gender and sexual minorities' rights within the African human rights system - Rajen, Narsinghen (University of Pretoria, 2021)
Mini Dissertation (LLM (Human rights and Democratisation in Africa))--University of Pretoria, 2021.